Humpy shrimp (Pandalus goniurus) from the western Bering Sea: a method of estimating the annual increment - B. G. Ivanov (12166385); D. A. Stolyarenko (12166343) (1995)
Length-based approaches for the analysis of population age/growth parameters are reviewed and a new method of succession is proposed for shrimp growth studies. The method is based on an analysis of the dynamics of the size composition of the population. The observations used to develop the model were length-frequency distributions derived from trawl surveys conducted in the Gulf of Anadyr in several years between 1972 and 1979. The model describing the observations is based on two assumptions: (a) succession of generation strength ratios, and (b) linear growth pattern. The succession method reduces the problem of estimating the average annual increment for generations well represented in samples to that of estimating the parameters of a non-linear error-in-variables regression model. The proposed model is considered as the first in a hierarchy of models for studying the age composition of a population. The applicability of the method is discussed.